Effect of processing temperature on structure and properties of microinjection moulded thermoplastic polyurethane/multiwalled carbon nanotube composites. (June 2015) - Li, D.; Zhai, T.; Gong, Q.; Fei, G.; Xia, H.
Abstract : Thermoplastic polyurethane (TPU)/multiwalled carbon nanotubes (MWCNTs) composites were prepared through twin extrusion and microinjection moulding. The effect of processing temperature on the structure and properties of composites were studied. Scanning electron microscopy and rheological test reveal the realisation of well dispersion and network formation of carbon nanotube (CNT) in TPU. Enhanced electrical conductivity has been found with the increasing mould temperature from 25 to 150°C, post-moulding thermal treatment under 180°C for 1 h leads to a significant increase in the electrical conductivity by over three orders of magnitude for 5 wt-%MWCNT filled TPU composites. Images (SEM and TEM) characterise the morphology of CNT network under low and high temperatures and the microcontact reconstruction of CNT network is proposed to explain the enhancement of electrical conductivity. The increased crystallinity of TPU leads to the enhancement of tensile strength and Young's modulus of composites after thermal treatment.